Study on The Uprooting Force for Cassava Harvesting - Agus Haryanto; Mochamad Zakky; Budianto Lanya (Jurnal Keteknikan Pertanian, 2022)
Harvesting of cassava is still mostly done manually by pulling cassava stems that are ready to be harvested. This study aimed to determine the amount of force required to pull cassava stems. The research was conducted on farmer's land in Bandar Agung Village, Bandar Sakti District, Central Lampung Regency. A sample of 50 cassava trees was selected to represent the center and four edges of 1-ha area sizing of 50-m x 200-m. Measurement of the pulling force of cassava was carried out using a winch supported by a triangular frame of iron pipe and equipped with a 100-kg chicken scale and rope. Parameters included force to uproot cassava stem, soil moisture content, soil hardness, stem circumference, plant height, and cassava tuber weight. The results showed that the uprooting force of cassava stem ranged from 20 kg (196 N) to 70 kg (686 N) with an average of 44.9 kg (440.2 N). The results also showed that the pulling force of cassava decreased with increasing soil moisture content with a range between 196 kN at soil moisture 15,9% and 686 kN at soil moisture 10%. Factors of plant height, stem circumference, and tuber weight also had a positive effect on the pulling force of cassava.